The occurrence of Upper Jurassic limestones in Cracow area and examples of their usage in the city architecture - Majer-Durman, Agnieszka (Geotourism/Geoturystyka, 2018)
This article presents basic information on the of Upper Jurassic limestones in the Cracow area and their exploitation in the past as well as providing some examples of their usage in the architecture of the city. Also, a proposal is presented of geotouristic trail to the Upper Jurrasic limestone a quarries located within the city area and through the most interesting architectural objects in Cracow, in which these limestones were used.